Revealing Religious Moderation: Hermeneutics Study in Al- Qur'an and Tripitaka Scripture - Fadillah, Nur Aisyah; Suci, Perwita (UIN Syarif Hidayatullah Jakarta, 2024)
This study examines the role of religious moderation in strengthening unity amid the diversity of Indonesian society, which is rich in ethnic, linguistic, and religious variations focusing on Islam and Buddhism. Using a hermeneutic and qualitative approach that combines theoretical, philosophical, and critical analysis, this study explores the principles of religious moderation as depicted in the Qur’an and the Tripitaka. It aims to discover ways to manage diversity in Indonesia and prevent religious conflicts, contributing to scholarly discussion on how religious moderation can support peaceful Coexistence in a diverse society. The finding highlights the support of Islam and Buddhism for the concept of moderation and their rejection of extremism, which is in line with the national principles of “Unity in diversity” (Bhinneka Tunggal Ika). The study concludes that implementing religious moderation based on tolerance and mutual respect is key to maintaining harmony and avoiding inter-religious friction, offering a practical framework for more inclusive social integration.